A NEW SUBGENUS AND TWO NEW SPECIES OF TRECHUS FROM ETHIOPIA (Coleoptera, Carabidae) - Magrini, Paolo; Quéinnec, Eric; Vigna Taglianti, Augusto (Fragmenta entomologica, 2012)
Two new species of Trechus from the Oromia Province (Ethiopia) are described in the present note. In the first part we describe Archeotrechus, a new microphtalmic Trechus, characterized by the dilation of only the first tarsal segment in males and by the aedeagus with the dorsal part amost completely divided into two lobes: a sclerified connection exists only in the region of the basal ostium. To this subgenus we ascribe the new species Trechus (Archeotrechus) relictus, from the area of Mt. Sgona (Batu), of yellow-brown colour, rather flattened, with non sinuate pronotum and blunt fore and hind angles; two discal setae in the third stria. The aedeagus is much elongated, with a spherical apical button, copulatory piece triangular, lanceolate, with a sharp apex, little sclerified and very simple, typical of ancestral forms, like for instance Minitrechus Vigna Taglianti & Magrini, 2009. The female gonostyli, short and curved, bear at the apex two big setae on the inner edge. In the second part of the note we describe Trechus (s. str.) oromiensis, a new species of bipartitus Group (sensu novo), characterized by the presence of only one discal seta on elytra and by peculiar features of the aedeagus.